English First Additional Language learners’ challenges in the implementation of process writing in Grade 10 - Audrey , Thaba Ramokone; Molotja, Tsebe Wilfred (International Journal of Membrane Science and Technology, 2023)
This paper seeks to explore English First Additional Language learners’ challenges in the implementation of process writing. The qualitative method was adopted, whereby document analysis and semi structured interview methods were used. The EFAL teacher and six learners from an identified secondary school were interviewed and learners’ essays were reviewed. The study revealed that learners write essays that have no effective introduction, weak idea support (ideas in all the paragraphs were not linked), and poor conclusions. Learners are challenged with organisation of ideas in sentences and paragraphs; omission of words which affect the message conveyed; punctuations and lack of vocabulary. It was also evident that teachers do not successfully implement the process of writing in the classroom. There is a lack of teaching and assessment of essay writing skills in the classrooms. Therefore, this paper recommends that the Department of Education arrange ongoing training for teachers on the implementation of process writing and modern methods of lesson delivery. Learners should be given more practical writing activities, engage in the writing process, and given the opportunity to collaborate with the teacher or their skilled peers to improve their writing skills.